Morphometry in Classification of Hippocampal Sclerosis - Güner, Güneş; Söylemezoğlu, Figen (Acta Medica, 2022)
Hippocampal sclerosis (HS) is evaluated in 3 categories by the latest (2013) ILAE classification. The distinction between these categories rely on the histopathological assessment of pyramidal neuron loss in 4 CA sectors. In order to evaluate neuron loss assessment done manually by a neuropathologist, cell counts were carried out from representative photomicrographs of each section. NeuN immunohistochemistry was applied on hippocampus sections of 28 samples of epilepsy surgery, photographed at x100 magnification to represent each of the 4 sectors, and neuron density was calculated per photo. This density data was compared to the pathology reports’ diagnoses. HS type 1 cases were predominant (n=23) with few type 2 and type 3 cases (3 and 2, respectively). Percentage of neuron loss calculated per photos, ILAE classification guidelines and pathological diagnoses rendered without any calculation were relatively well-correlated; with HS type 2 and 3 displaying slight changes from recommendations. Data also display accurate pathological diagnoses of HS without special equipment or cell density calculation. HS types 2 and 3 in Turkey may display variant cell density properties which may warrant further clarification.